The Link between Physical Evidence, Customer Satisfaction and Customer Loyalty: An Empirical Analysis - Idrus, Nanda Lutfiah; Yendra, Yendra; Marihi, La Ode (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study aims to examine the effect of physical evidence on customer loyalty mediated by customer satisfaction at Shadow Edge Park Jayapura Cafe. The hypothesis is that customer satisfaction mediates the impact of physical evidence on customer loyalty. Research Design and Methodology: The method used was descriptive quantitative with a survey design. Data were collected from 120 Shadow Edge Park Jayapura Cafe consumers through questionnaires. The data were analyzed using Structural Equation Modeling (SEM) with AMOS 22 software. Findings and Discussion: The results show that physical evidence positively and significantly influences customer satisfaction, mediating this influence on customer loyalty. The findings support the Servicescapes theory, suggesting that physical elements such as interior design, cleanliness, and ambiance of the café are key factors that influence customer satisfaction and loyalty. Implications: Café managers should focus on managing physical evidence elements to increase customer satisfaction and loyalty. Further research is needed to explore factors such as social interaction and service quality that may influence customer loyalty. Future studies could expand geographic and cultural coverage to test the consistency of these findings.